2022
DOI: 10.1371/journal.pntd.0010714
|View full text |Cite
|
Sign up to set email alerts
|

High infectivity and unique genomic sequence characteristics of Cryptosporidium parvum in China

Abstract: Zoonotic Cryptosporidium parvum infections are mainly caused by IIa and IId subtypes. As most biological characterizations have been performed on IIa subtypes, the biological and genetic characteristics of IId subtypes in China are not clear. We evaluated the infection and genetic characteristics of IId isolates in interferon-γ-knockout mice using qPCR to quantify oocyst shedding, histological examination to monitor pathological changes and comparative genomic analyses to identify infectivity and virulence-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…The IId-HLJ isolate of the IIdA20G1 subtype was initially obtained from a dairy calf on a farm in Heilongjiang (HLJ), China and maintained through passages in GKO mice. This isolate has higher infectivity and some unique genomic sequence characteristics in comparison with the IIaA17G2R1-Waterborne isolate as previously described (25). Oocysts of nonhuman primate-adapted C. hominis isolates of the IbA12G3, ImA20, InA17 subtypes were initially obtained from crab-eating macaques (Macaca fascicularis) in China using sucrose and cesium chloride gradient centrifugations (36,37).…”
Section: Discussionmentioning
confidence: 98%
“…The IId-HLJ isolate of the IIdA20G1 subtype was initially obtained from a dairy calf on a farm in Heilongjiang (HLJ), China and maintained through passages in GKO mice. This isolate has higher infectivity and some unique genomic sequence characteristics in comparison with the IIaA17G2R1-Waterborne isolate as previously described (25). Oocysts of nonhuman primate-adapted C. hominis isolates of the IbA12G3, ImA20, InA17 subtypes were initially obtained from crab-eating macaques (Macaca fascicularis) in China using sucrose and cesium chloride gradient centrifugations (36,37).…”
Section: Discussionmentioning
confidence: 98%
“…Differences in host preference and virulence have been reported between GP60 subtype families of C. parvum and C. hominis , respectively (14, 15). Mice experimentally infected with different GP60 subtypes of C. parvum have shown significant differences in infection intensity, duration, and pathogenicity (20). However, few studies have been undertaken to examine the biological processes of GP60-mediated host cell infection.…”
Section: Discussionmentioning
confidence: 99%
“…We have generated genetic crosses of fluorescently tagged C. parvum isolates IIdA20G1-HLJ and IIdA19G1-GD, which differ significantly in infectivity, infection pattern, and virulence in GKO mice. 9 Linkage mapping using BSA of genomes collected over the course of infection with F1 progeny has identified three QTL containing 26 genes that potentially control the virulence difference between the two isolates. Reverse genetic studies of the two best candidates have confirmed the involvement of SKSR1, a secretory small granule protein encoded by a polymorphic subtelomeric gene, in C. parvum virulence.…”
Section: Discussionmentioning
confidence: 99%
“…4,10 However, the genetic determinants of Cryptosporidium virulence and infectivity are not clear, although the results of comparative genomic analysis have provided some clues. 9 In Plasmodium falciparum and Toxoplasma gondii, linkage mapping of genetic crosses of isolates has been effective in the study of virulence factors. 11,12 It has led to the identification of P. falciparum erythrocyte membrane protein 1 (PfEMP1) and several rhoptry proteins as major determinants of virulence in P. falciparum and T. gondii, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation